Measuring Readability of Farm Information Published in Newspapers - G.R Uike; D.M. Mankar; R.G. Mardane (Journal of Agricultural Extension Management, 2025)
Print media have been accepted as an important means of communication. Printed words are effective as compared to other mass media because they hold certain merits. These words help the communicator to think, organize ideas and choose better so that the reader can understand the ideas easily (Salunkhe and Sawant, 1984). Printed words are largely used for communicating useful farm information to literate farmers, thus catering to the needs of farming communities. Printed material is being used increasingly with steady improvement in literacy rate in the country (Anonymous, 2002)